Pengaruh Likuiditas, Kualitas Aset, Sensitifitas dan Efisiensi Terhadap Profitabilitas Pada Bank Pembangunan Daerah Devisa - Muhammad Akbar Sidiq (Cakrawala Repositori IMWI, 2023)
The purpose of this study was to analyze Loan to Deposit Ratio (LDR), Investing Policy Ratio (IPR), Non Performing Loans (NPL), Non Performing Earning Assets (APB), Interest Rate Ratio (IRR), Net Open Position (NOP), Operating Costs to Operating Income (BOPO) and Fee Based Income Ratio (FBIR) to Return On Assets (ROA) at Foreign Exchange Regional Development Banks registered with OJK. PT BPD Riau Kepri, PT BPD South Sumatra and Bangka Belitung, PT BPD East Kalimantan and North Kalimantan and PT BPD South Sulawesi and West Sulawesi; are the samples of this study using purposive sampling method. This study uses secondary data from financial reports for the period quarter I, 2018 to quarter II, 2022. The data analysis technique is descriptive analysis and uses multiple linear regression analysis. The results of this study reveal that simultaneously LDR, IPR, NPL, APB, IRR, PDN, BOPO and FBIR have a significant effect on ROA. Partially, LDR, IPR, APB, IRR BOPO and FBIR have an insignificant effect on ROA, while NPL has a significant negative effect on ROA.